2017
DOI: 10.1016/j.vaccine.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of enhancer agonist human cytotoxic T-cell epitopes of the human papillomavirus type 16 (HPV16) E6/E7

Abstract: Human papillomavirus (HPV) is associated with the etiology of cervical carcinoma, head and neck squamous cell carcinoma, and several other cancer types. Vaccines directed against HPV virus-like particles and coat proteins have been extremely successful in the prevention of cervical cancer through the activation of host HPV-specific antibody responses; however, HPV-associated cancers remain a major public health problem. The development of a therapeutic vaccine will require the generation of T-cell responses di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…Many studies have focused on enhancing immunogenicity using immune stimulating agents or adjuvants to avoid this problem. Another solution is the use of agonist epitopes [ 94 ]. Epitope immunogenicity is a crucial factor in vaccine development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have focused on enhancing immunogenicity using immune stimulating agents or adjuvants to avoid this problem. Another solution is the use of agonist epitopes [ 94 ]. Epitope immunogenicity is a crucial factor in vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of previous studies have used in silico analyses for epitope prediction against different pathogens [ 94 , 96 , 98 103 ]. However, the prediction of T cell epitopes inducing strong responses has remained a big challenge.…”
Section: Discussionmentioning
confidence: 99%
“…They introduced 14 peptides (9 to 43 amino acids) which can be used as potent regions in therapeutic vaccines (Singh et al 2016). Tsang et al analyzed HPV16 E6 and E7 proteins and found six immunogenic epitopes, as well (Tsang et al 2017). While the oncogenic activities of E6 and E7 were well known, the role of E5 is still rather unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For T2 cells, 3-35 μM of recombinant β2M was also added. As a control, the well-characterized peptide YMLDLQPET (YML) (66) derived from the E7 protein expressed by HPV-16 was used.…”
Section: Screening Of Phage Scfv Specific For Ebv-lmp2(clg)/hla-a0201mentioning
confidence: 99%